2013
DOI: 10.4028/www.scientific.net/amm.465-466.191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Content and Tween 80 to the Stability of Emulsified Biodiesel

Abstract: Emulsified biodiesel are often stabilized using a combination ratio water, biodiesel and surfactant in achieving stable emulsions. The objective of this study was to evaluate the long-term stability of three phase oil-in-water-in-oil (O/W/O) with respect to the water content and Tween 80. Biodiesel emulsions containing 5 mL, 10 mL and 15 mL water were produce with combination of 95 mL, 90 mL and 85 mL B20 (80 % diesel + 20 % biodiesel) and surfactant by using a mechanical stirrer machine. The experimental resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The presence of curvature in the surface response curve of B*C indicated that the interaction term had a significant effect on particle diameter and PDI of the prepared nano-formulations ( p ≥ 0.05). It is likely that the surfactant molecules reached an optimum concentration and achieved maximum coverage, and rapidly adsorbed onto the surface of the nano-droplets, therapy reducing the interfacial tension at the oil-water interface, resulting in the formation of smaller droplets (Qian & McClements, 2011 ; Witayaudom & Klinkesorn, 2017 ; Aziz et al., 2013 ; Joung et al., 2016 ; Manchun et al., 2014 ). In addition, the presence of maximum PG: T80 ratio (0.17%) as a co-surfactant worked in combination with T80 to enhance the flexibility of the interfacial film by positioning itself between the T80 tails; this reduced clustering and promoted the production of a homogenous size of oil nanodroplets in the aqueous phase (Polychniatou & Tzia, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of curvature in the surface response curve of B*C indicated that the interaction term had a significant effect on particle diameter and PDI of the prepared nano-formulations ( p ≥ 0.05). It is likely that the surfactant molecules reached an optimum concentration and achieved maximum coverage, and rapidly adsorbed onto the surface of the nano-droplets, therapy reducing the interfacial tension at the oil-water interface, resulting in the formation of smaller droplets (Qian & McClements, 2011 ; Witayaudom & Klinkesorn, 2017 ; Aziz et al., 2013 ; Joung et al., 2016 ; Manchun et al., 2014 ). In addition, the presence of maximum PG: T80 ratio (0.17%) as a co-surfactant worked in combination with T80 to enhance the flexibility of the interfacial film by positioning itself between the T80 tails; this reduced clustering and promoted the production of a homogenous size of oil nanodroplets in the aqueous phase (Polychniatou & Tzia, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The emulsified fuel was produced using a mechanical stirrer machine which is commonly used in the industry for emulsion preparation [9]. Both surfactant Span 80 and Tween 80 were added into biodiesel B20 and water using method that utilize in previous study [5]. The properties of biodiesel B20 were shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Biodiesel is one of the main alternative fuel due to their good properties as diesel engine fuel and can be utilized in diesel engines [3,4]. Commonly, biodiesel contains around 10 to 15 % of oxygen content which will enhance burning efficiency, reduce emission of PM, CO and other gaseous pollutants [5]. However, under a high combustion temperature, there will be larger NOx formation, which is around 10 % higher than fossil diesel due to higher oxygen content [6].…”
Section: Introductionmentioning
confidence: 99%
“…By using the method that utilized by Aziz, Jusoh [17], both surfactant Span 80 and Tween 80 were added into the mixture of biodiesel B5 and water to increase the affinity and reduce the interfacial between the water and oil phases. The test fuels were biodiesel (B5), B5 emulsified with 4% water (BW4), B5 emulsified with 6% water (BW6), and B5 emulsified with 8% water (BW8).…”
Section: Preparation Of Emulsified Biodieselmentioning
confidence: 99%